The Relationship Of Family Support With Blood Pressure Control Behavior In Hypertensive Patients In The Working Area Of Uptd Puskesmas Kerambitan I - Putu Reymelda; Ni Wayan Trisnadewi; Ketut Lisnawati (International Journal of Health Engineering and Technology, 2026)
Blood pressure control behavior is an effort made by people with hypertension to maintain blood pressure stability and prevent complications. The success of these behaviors is greatly influenced by family support, which plays a role in providing motivation and practical assistance in maintaining a healthy lifestyle consistently. This study aims to determine the relationship between family support and blood pressure control behavior in people with hypertension. The study used a correlational descriptive design with a cross sectional approach. The study population amounted to 1,435 hypertensive patients, with a sample of 94 respondents selected using purposive sampling techniques. Data collection used family support questionnaires and blood pressure control behavior questionnaires. Data analysis using the Spearman's Rho test. The results showed that the majority of respondents had good family support, namely 54 people (57.4%) and good blood pressure control behavior as many as 50 people (53.2%). The results showed a p-value of 0.000 (<0.05) and a correlation coefficient of 0.627, which means that there is a strong and significant relationship between family support and blood pressure control behavior. Family support has an important contribution in helping people with hypertension carry out optimal blood pressure control behaviors, because family involvement is an essential factor that increases the motivation, discipline, and ability of people with hypertension to maintain healthy living behaviors consistently.